PERAN STRATEGI PEMASARAN DALAM MENINGKATKAN PERTUMBUHAN EKONOMI: ANALISIS SINTESIS TERHADAP UMKM DI KOTA DUMAI - Novelma Lastri; Variza Aditiya; Dwi Hartutik; Suprasman Suprasman; Said Mustafa (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in Indonesia’s economy, including in Dumai City; however, they continue to face challenges in expanding market reach and enhancing competitiveness, particularly in adopting digital marketing technologies. This study aims to synthesize relevant literature on digital marketing strategies and their impact on MSME economic growth in Dumai City. A qualitative approach using a literature review method was employed to analyze previous studies related to digital marketing, e-commerce, and digital transformation among MSMEs. The findings indicate that digital marketing implementation significantly improves sales performance, product visibility, and customer interaction, with some MSMEs reporting substantial revenue increases, even exceeding twofold growth over the past two years. The utilization of social media platforms and digital marketplaces has become a key driver in expanding market access beyond local geographic boundaries. Nevertheless, challenges remain, including limited digital literacy, infrastructure constraints, and underutilization of websites as marketing tools. This study highlights that integrated digital marketing strategies supported by continuous training and institutional assistance are essential to strengthen MSME competitiveness and achieve sustainable growth in the digital era. Keywords: MSMEs, digital marketing, e-commerce, digital transformation, Dumai City. Abstrak: Usaha Mikro, Kecil, dan Menengah (UMKM) memiliki peran strategis dalam perekonomian Indonesia, termasuk di Kota Dumai, namun masih menghadapi berbagai tantangan dalam memperluas jangkauan pasar dan meningkatkan daya saing, khususnya dalam adopsi teknologi pemasaran digital. Penelitian ini bertujuan untuk mensintesis literatur terkait strategi pemasaran digital dan dampaknya terhadap pertumbuhan ekonomi UMKM di Kota Dumai. Metode yang digunakan adalah pendekatan kualitatif melalui tinjauan pustaka (literature review) dengan menganalisis berbagai penelitian relevan mengenai digital marketing, e-commerce, serta transformasi digital pada UMKM. Hasil kajian menunjukkan bahwa penerapan pemasaran digital secara signifikan meningkatkan penjualan, visibilitas produk, serta interaksi dengan konsumen, bahkan beberapa UMKM melaporkan peningkatan omzet hingga lebih dari dua kali lipat dalam dua tahun terakhir. Pemanfaatan media sosial dan marketplace digital menjadi faktor utama dalam memperluas pasar di luar batas geografis lokal. Namun demikian, keterbatasan literasi digital, infrastruktur, serta pemanfaatan website yang belum optimal masih menjadi tantangan utama. Penelitian ini menegaskan bahwa strategi pemasaran digital yang terintegrasi, didukung oleh pelatihan dan pendampingan berkelanjutan dari pemerintah dan pemangku kepentingan, sangat penting untuk meningkatkan daya saing dan pertumbuhan berkelanjutan UMKM di era digitalisasi. Kata kunci: UMKM, pemasaran digital, e-commerce, transformasi digital, Kota Dumai.